2020
DOI: 10.21203/rs.3.rs-37618/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of COVID-19 pandemic on general surgical emergencies: Are some emergencies really urgent? Level 1 Trauma center experience

Abstract: Purpose: We aimed to investigate the effect of COVID-19 pandemic on general surgical emergencies. On the other hand, we analyzed the effectiveness of the measures we have taken and the incidence of COVID-19 of patients and healthcare professionals.Method: In the pandemic period between March 14 and May 15, 2020, and in the same period of the previous year, the files of patients who underwent emergency surgery and followed up nonoperatively were reviewed retrospectively. The incidence of COVID-19 was questioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…16,30,31 Surek et al revealed that while hospitalizations for acute cholecystitis and uncomplicated appendicitis were markedly reduced during the COVID-19 pandemic, hospitalizations for complicated appendicitis and acute mechanical intestinal obstruction were increased, and the mortality from emergency surgery also increased. 30 A study of out-of-hospital cardiopulmonary arrest (OHCA) in South Korea found that the time from arrival at the scene to the start of activities by EMS personnel and transport time were increased by the increased requirement for personal protective equipment in the prehospital situation and by securing isolation wards. 31 A study in Japan also found that the rate of bystander cardiopulmonary resuscitation was decreased for OHCA patients during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…16,30,31 Surek et al revealed that while hospitalizations for acute cholecystitis and uncomplicated appendicitis were markedly reduced during the COVID-19 pandemic, hospitalizations for complicated appendicitis and acute mechanical intestinal obstruction were increased, and the mortality from emergency surgery also increased. 30 A study of out-of-hospital cardiopulmonary arrest (OHCA) in South Korea found that the time from arrival at the scene to the start of activities by EMS personnel and transport time were increased by the increased requirement for personal protective equipment in the prehospital situation and by securing isolation wards. 31 A study in Japan also found that the rate of bystander cardiopulmonary resuscitation was decreased for OHCA patients during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%